MENJAWAB TUDUHAN IDEOLOGISASI DALAM TAFSIR AHKAM: Telaah atas Kitab AsbÄb IkhtilÄf al-MufasirÄ«n fÄ« TafsÄ«r á¾¹yÄt al-Aá¸¥kÄm - Abdul Wadud Kasful Humam (STAI AL-ANWAR SARANG, 2020)
This article examines the answer of Abdul Ilāh Ḥūri to the accusation of ideologization in tafsīr ayāt aḥkām (Qur’anic exegesis on the legal verses) through his work Asbāb Ikhtilāf al-Mufassirīn fī Tafsīr Ᾱyāt al-Aḥkām. The tendency to ideologize these schools of tafsīr can be understood not only because of the writer's background as a demonstrative school activist, but other factors are also very influential on the resulting tafsīr ayāt aḥkām products, such as: differences in using the rules of al-'ibrah bi 'umūm al-lafẓi lā bi khuṣūṣ al-sabab or vice versa, differences in choosing qirā'at, differences in interpreting siyāq (context) or in his term that is called mā fī al-Qur'ān and mā ḥaula al-Qur'ān.